Publication Ethics and Publication Malpractice Statement (Semiconductor Physics Quantum Electronics & Optoelectronics, 2014)
All editors, reviewers and authors, should be familiarized and take into account the Publication Ethics and
Publication Malpractice Statement of the international journal “Semiconductor Physics, Quantum Electronics and
Optoelectronics”. This statement is based on the COPE Code of Conduct for Journal Editors.